Wyzwania stojące przed początkującymi nauczycielami nauczania specjalnego przygotowującymi zindywidualizowane programy edukacyjne dla uczniów ze specjalnymi potrzebam - Bar, Nava (Studia Edukacyjne, 2019)
The individualized education program (IEP) constitutes a main component in the formation and adjustment of special education services, the supports, and the teaching for special needs students. It is based on the recognition of the differences among special needs students and the need to provide an answer to this diversity. This article presents findings of a longitudinal qualitative study, conducted among thirty special education novice teachers (SENTs) in Israel. The study examined the perceptions of the SENTs on the continuum of the induction year, regarding the obligation, anchored in the Special Education Law (1988), to build IEPs to their special needs students – already in their first steps of their entry into teaching, and the support they received for coping with this challenge.